A Comparative study of Shakespeare and Hafiz’s sonnets, based on the Horace’s motif of Carpe Diem - Comcar, Milad; Movaghati, Sina (Journal of English Language and Literature (ISSN: 2368-2132), 2015)
Carpe Diem which means “enjoy, seize, use, and make use of” is a term taken from ode I. XI of Horace and has become a very common motif in literature ever since. Many poets throughout history have used this motif. But what are the main tenets of the motif in Horace’s odes? This article tries to show the main tenets of Carpe Diem according to Horace. These tenets are: tomorrow, living in the present and drinking wine; we try to apply the discussed elements on two sonnets of the greatest sonneteers of all times in two different countries. That of England’s William Shakespeare’s sonnet 73 and that of Persia’s Hafiz’s sonnet 473; we strive to see to what extent time has affected the concept of Carpe Diem in the poems; and to what extent the sonnets of Shakespeare and Hafiz followed the pattern of Horace’s Carpe Diem.